PENINGKATAN KEMAMPUAN MENGENAL ANGKA ANAK USIA DINI MELALUI PERMAINAN LOMPAT ANGKA DI TAMAN KANAK KANAK PERTIWI II KABUPATEN LIMA PULUH KOTA - Tati Murni; Indra Yeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low ability of early childhood learners to recognize numbers at TK Pertiwi II, Lima Puluh Kota Regency. Most children experienced difficulties in mentioning number sequences, recognizing number symbols, and matching quantities with the correct number symbols. The purpose of this study was to improve children's number recognition skills through a number-jumping game. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 15 children aged 5–6 years. Data were collected through observation, documentation, and field notes. The findings indicated a significant improvement in children's number recognition skills. The percentage of children achieving the categories of Developing as Expected and Very Well Developed increased from 33% in the initial condition to 60% in Cycle I and reached 86% in Cycle II. These results demonstrate that the number-jumping game is effective in improving number recognition skills in early childhood education.